Is there a signalling role for public wages? Evidence for the euro area based on macro data - Javier J. Pérez; Jesús Sánchez (European Central Bank (ECB), 2010)
Do public sector wages exert pressures on private sector wages, or has the private sector a leadership role in wage setting? This paper tries to isolate the pure signalling effect that one sector might exert on the other by controlling for other determinants of wages (prices, productivity, institutions) for the main euro area economies (Germany, France, Italy and Spain) and the periods 1980-2007 and 1991-2007. It exploits available quarterly information not yet used in the literature, and combines different data sources in the framework of mixed-frequencies time series models. The quarterly frequency of our data allows us to check the existence of purely intra-annual links between public and private sector wages (signalling effect). There is strong evidence of public wages' leadership, either in conjunction with bi-directional links from the private sector (Germany and Spain) or pure public wage leadership (France in the sample 1991-2007, Italy for within-the-year linkages).
Keywords: C32; C53; J30; J51; J52; E62; E63; H50; H6; 330; causal graph; causality; government wages; Mixed frequency data; private sector wages; signalling; Vergütungssystem im öffentlichen Dienst; Signalling; Eurozone; EU-Staaten